Permanent Leadless Cardiac Pacemaker Therapy: A Comprehensive Review. Issue 15 (11th April 2017) - Tjong, Fleur V.Y.; Reddy, Vivek Y.
Abstract : A new technology, leadless pacemaker therapy, was recently introduced clinically to address lead- and pocket-related complications in conventional transvenous pacemaker therapy. These leadless devices are self-contained right ventricular single-chamber pacemakers implanted by using a femoral percutaneous approach. In this review of available clinical data on leadless pacemakers, early results with leadless devices are compared with historical results with conventional single-chamber pacing. Both presently manufactured leadless pacemakers show similar complications, which are mostly related to the implant procedure: cardiac perforation, device dislocation, and femoral vascular access site complications. In comparison with conventional transvenous single-chamber pacemakers, slightly higher short-term complication rates have been observed: 4.8% for leadless pacemakers versus 4.1% for conventional pacemakers. The complication rate of the leadless pacemakers is influenced by the implanter learning curve for this new procedure. No long-term outcome data are yet available for the leadless pacemakers. Larger leadless pacing trials, with long-term follow-up and direct randomized comparison with conventional pacing systems, will be required to define the proper clinical role of these leadless systems. Although current leadless pacemakers are limited to right ventricular pacing, future advanced, communicating, multicomponent systems are expected to expand the potential benefits of leadless therapy to a larger patient population. Abstract : Supplemental Digital Content is available in the text.